AN ANALYSIS OF THE RELATIONSHIP BETWEEN EARNINGS AND CORPORATE TAXES ON DIVIDEND POLICY OF COMPANIES IN SRI-KEHATI INDEX - Etheldreda Gladys Salvatori; Robiyanto Robiyanto; Harijono Harijono (Universitas Islam Nahdlatul Ulama Jepara, 2020)
Objective: This study examines the effect of earnings and corporate taxes role on the company's dividend policy in the SRI-KEHATI Index. In this research, dividend policy means dividends paid proportion to shareholders. Earnings are estimated by four financial ratios namely contributed capital ratio, prior year-earnings, sales growth, and return on assets.Research Design & Methods: The sample is taken according to purposive sampling with the criteria of the consistency of the company listed in the SRI-KEHATI Index during 2014-2017 and routinely distributes annual dividends, finally 14 companies are taken from 33 companies. Panel data were examined with the assistance of Eviews 9.0 software. Data collected from the company's financial statements and measured using a formula adopted from earlier research. Findings: Empirical results found that capital ratio, prior year-earnings, sales growth, and corporate taxes did not significantly affect the dividend payout ratio. While return on assets has a positive effect on dividend payout ratio. Companies that grow well will need more funds to cover their financing and try to keep up their income proportion, one way is to pay a constant dividend, lower, or even zero dividends. Limitations & Recommendations: This finding recommends that investors should pay attention to company profitability by measuring return on assets. Future research can use the new stock index’s constituents such as IDX High Dividend 20 and include other factors that indicated to determine dividend policy. Contribution & Value Added: This result contributes to the financial literature, especially related to the dividend policy of public listed companies in Indonesia. Practically, investors can use this result as additional information in investment decisions.